The Gut Microbiota and Mucosal T Cells - Smith, Patrick; Garrett, Wendy (Frontiers in Microbiology, 2011)
It is intuitive that immune cells in the gut may require microbiota-derived cues for their differentiation. The proximity between host and microbe in the intestine would seemingly necessitate co-adaptation. However, it has been challenging to determine the members and features of the gut microbiota that influence immune system development and function. The recent identification of immunomodulatory members of the commensal microbiota is providing insight into the dependence of select, intestinal immune cell subsets on specific microbial species. In this review, we focus on the gut microbiota’s influence on the development and function of mucosal T cells subsets, specifically intraepithelial lymphocytes and lamina propria CD4 T cells.